2019
DOI: 10.21273/hortsci13418-18
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Fatty Acid Profiles of Macadamia Nuts

Abstract: The kernel of the macadamia nut (Macadamia integrifolia and M. tetraphylla) is very high in oil, accounting for about three -quarters of their mass. In the current investigation, oil extracts from 20 breeding accessions and 14 cultivars had a range of 12.3% to 17.0% saturated fat, averaging 14.2%. Although all samples were found to be very high in ''healthy'' monounsaturated fats, the level of saturated fat slightly exceeds that of many other nuts that are able to make qualified health claims. The lowest satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Our results showed that small macadamia kernels have a fatty acid profile that is at least as healthy as large macadamia kernels. However, the differences in fatty acid profile between small and large kernels were much less than the differences between macadamia cultivars [27,72,73] and between tree-nut species including almond, hazelnut, macadamia, pecan, pistachio and walnut [4,9]. All these nuts are considered beneficial for reducing the risk of cardiovascular disease because of their high levels of unsaturated fatty acids [1,2,7,10,14,[74][75][76][77][78][79].…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that small macadamia kernels have a fatty acid profile that is at least as healthy as large macadamia kernels. However, the differences in fatty acid profile between small and large kernels were much less than the differences between macadamia cultivars [27,72,73] and between tree-nut species including almond, hazelnut, macadamia, pecan, pistachio and walnut [4,9]. All these nuts are considered beneficial for reducing the risk of cardiovascular disease because of their high levels of unsaturated fatty acids [1,2,7,10,14,[74][75][76][77][78][79].…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…High levels of cross-paternity confirmed that many macadamia cultivars are predominantly outcrossing. Macadamia growers may need to closely inter-plant cultivars and manage beehives to maximise cross-pollination.Plants 2020, 9, 228 2 of 14 also a valuable source of calcium, iron and zinc, which can be absorbed insufficiently during phases of high dietary demand such as infancy, childhood, adolescence, pregnancy and breastfeeding [16][17][18][19][20][21].The fatty acid composition and nutrient concentrations of tree-nut kernels can vary greatly among cultivars [9,[22][23][24][25][26][27][28]. Fatty acid composition and nutrient concentrations can also vary within almond or pistachio cultivars because of differences in the pollen parentage of individual kernels [22][23][24][25]29,30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Areas of research included propagation, tree physiology, soils and nutrition, pollination biology, pest and disease biology, orchard management, genetics and breeding, developing production areas, and product development. Seven of the presentations are published in this special section Hardner et al, 2019;Howlett et al, 2019;O'Connor et al, 2019;O'Hare et al, 2019;Toft et al, 2019;Zhao et al, 2019).…”
Section: Summary Of Presentationsmentioning
confidence: 99%
“…Product development. Macadamia kernels contain 76% oil, of which 79% to 86% is mono-or poly-unsaturated and increasing levels could support opportunities for health claims (T.J. O'Hare et al, personal communication) (O'Hare et al, 2019). These authors report desaturation of C18:0 to C18:1 is much more efficient than for C16:0, suggesting that increasing the rate of elongation of C16:0 followed by increasing desaturation of C18:0 may be the most efficient strategy for producing greater unsaturated oils.…”
Section: Summary Of Presentationsmentioning
confidence: 99%